2009
DOI: 10.1007/s00167-009-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of non-contact anterior cruciate ligament injuries in soccer players. Part 1: Mechanisms of injury and underlying risk factors

Abstract: Soccer is the most commonly played sport in the world, with an estimated 265 million active soccer players by 2006. Inherent to this sport is the higher risk of injury to the anterior cruciate ligament (ACL) relative to other sports. ACL injury causes the most time lost from competition in soccer which has influenced a strong research focus to determine the risk factors for injury. This research emphasis has afforded a rapid influx of literature defining potential modifiable and non-modifiable risk factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
679
1
34

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 710 publications
(761 citation statements)
references
References 183 publications
(332 reference statements)
15
679
1
34
Order By: Relevance
“…A full appraisal of these topics is beyond the scope of this review and in some instances has already been conducted [71][72][73][74][75][76]. However, the importance of these variables to female soccer players and the potential impact on training, performance and injury risk should not be underestimated.…”
Section: ) Female Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…A full appraisal of these topics is beyond the scope of this review and in some instances has already been conducted [71][72][73][74][75][76]. However, the importance of these variables to female soccer players and the potential impact on training, performance and injury risk should not be underestimated.…”
Section: ) Female Differencesmentioning
confidence: 99%
“…Internal risk factors include anatomical, neuromuscular, biomechanical and hormonal variables [74,75]. Studies often concentrate on intrinsic risk factors as they can provide differentiation between the sexes.Evidence suggests the anatomy of the female knee, specifically a smaller intercondylar notch width and ACL, are contributing factors to an increased risk of ACL injury [74,75]. A link has been established between hypermobile individuals and higher risk of ACL injuries in female soccer and basketball players [122].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased leg stiffness is suggested to enhance rate of force development, locomotor kinematics and energy storage and utilisation (Brughelli and Cronin 2008), providing performance benefits of increased force output, movement speed and running economy (Butler et al 2003;Wilson and Flanagan 2008). Furthermore, it has been suggested that lower limb stiffness is an important injury protection mechanism (Alentorn-Geli et al 2009), with low levels of stiffness associated with soft tissue injuries (Hobara et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…It was not within the scope of this review to discuss the causes of any gender-related difference, since this has been done previously [3,38,41].…”
Section: Introductionmentioning
confidence: 99%